Consensus clinical recommendations for the management of plasma lipid disorders in the Middle East. (15th December 2016) - Al Sayed, Nasreen; Al Waili, Khalid; Alawadi, Fatheya; Al-Ghamdi, Saeed; Al Mahmeed, Wael; Al-Nouri, Fahad; Al Rukhaimi, Mona; Al-Rasadi, Khalid; Awan, Zuhier; Farghaly, Mohamed; Hassanein, Mohamed; Sabbour, Hani; et al.
Abstract: Background: Plasma lipid disorders are key risk factors for the development of atherosclerotic cardiovascular disease (ASCVD) and are prevalent in the Middle East, with rates increasing in recent decades. Despite this, no region-specific guidelines for managing plasma lipids exist and there is a lack of use of guidelines developed in other regions. Methods: A multidisciplinary panel of regional experts was convened to develop consensus clinical recommendations for the management of plasma lipids in the Middle East. The panel considered existing international guidelines and regional clinical experience to develop recommendations. Results: The panel's recommendations include plasma lipid screening, ASCVD risk calculation and treatment considerations. The panel recommend that plasma lipid levels should be measured in all at-risk patients and at regular intervals in all adults from the age of 20 years. A scoring system should be used to calculate ASCVD risk that includes known lipid and non-lipid risk factors. Primary treatment targets include low-density lipoprotein cholesterol and non-high-density lipoprotein cholesterol. Lifestyle modifications should be first-line treatment for all patients; the first-line pharmacological treatment targeting plasma lipids in patients at moderate-to-high risk of ASCVD is statin therapy, with a number of adjunctive or second-line agents available. Guidance is also provided on the management of underlying conditions and special populations; of particular pertinence in the region are familial hypercholesterolaemia, diabetes and metabolic dyslipidaemia. Conclusions: These consensus clinical recommendations provide practicing clinicians with comprehensive, region-specific guidance to improve the detection and management of plasma lipid disorders in patients in the Middle East. Highlights: Plasma lipid disorders are of increasing prevalence and concern in the Middle East. There is a lack of regional clinical guidelines. A regional, multidisciplinary expert panel has developed clinical recommendations. Recommendations are based on international guidelines and clinical experience. Guidance considers screening, risk levels, treatment and special populations.